Microfoams based on castor oil polyurethanes and vegetable fibers - Aranguren, Mirta Ines (2007)
This work was focused on the production and characterization of microcellular polyurethane (PU) composites reinforced with pine wood-fibers or with hemp, which can be applied to the manufacture of car interior panels, or acoustic insulation panels for the construction industry. The polymers selected for the study were crosslinked PUs, synthesized from a castor oil-based polyol, with the formulations adjusted to obtain different foaming levels. Microfoamed composites with preferential orientation were prepared from long hemp fibers. Also, samples with random arrangement of short hemp and wood fibers were obtained. The morphology of the composites was analyzed by scanning electron microscopy. The mechanical performance of the reinforced foams was studied through three point bending and dynamic mechanical tests.